2009
DOI: 10.1289/ehp.0900730
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity of Size-Fractionated Airborne Particulate Matter Collected at Different Distances from an Urban Highway

Abstract: BackgroundEpidemiologic studies have reported an association between proximity to highway traffic and increased cardiopulmonary illnesses.ObjectivesWe investigated the effect of size-fractionated particulate matter (PM), obtained at different distances from a highway, on acute cardiopulmonary toxicity in mice.MethodsWe collected PM for 2 weeks in July–August 2006 using a three-stage (ultrafine, < 0.1 μm; fine, 0.1–2.5 μm; coarse, 2.5–10 μm) high-volume impactor at distances of 20 m [near road (NR)] and 275 m [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 53 publications
7
78
1
Order By: Relevance
“…However, the toxicity of different volatility and size classes of PM is not well established in the current literature. For example, Cho et al (2009) reported no significant difference in the overall toxicity end points for PM samples collected at 20 and 275 m from an interstate highway. Further research is needed to better understand the toxicity and health impacts of different volatility and size classes of PM from different sources and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the toxicity of different volatility and size classes of PM is not well established in the current literature. For example, Cho et al (2009) reported no significant difference in the overall toxicity end points for PM samples collected at 20 and 275 m from an interstate highway. Further research is needed to better understand the toxicity and health impacts of different volatility and size classes of PM from different sources and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This spatial pattern is not observed for the pollutants most often investigated in impact assessments, such as PM10, PM2.5 (particulate matter up to 10 mm or 2.5 mm in size) or ozone. Furthermore, experimental studies show that the health effects of ultra-fine near-road particles are not necessarily the same as the effects of larger particles [8]. Therefore, common measurement strategies and health assessments may not adequately characterise near-road pollution and associated health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous epidemiological studies have demonstrated a positive association between exposure to aerosol particles and adverse respiratory consequences (Rogula-Kozlowska et al 2008;Klejnowski et al 2012). Evidence shows that the toxicological and carcinogenic effects of aerosol particles depend on their sizes and chemical compositions (Diociaiuti et al 2001;Cho et al 2009). Aerosol particles of a specific size range have distinct sources, formation mechanisms, and chemical compositions (Hering and Friedlander 1982;Huang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The continued increase in automobile exhaust emissions has caused severe air pollution problems (Chan and Yao 2008;Xue et al 2011;He and Lu 2012). Particulates originating from mobile sources are thought to be responsible for various adverse health effects, ranging from asthma to lung cancer and cardiopulmonary disease (Rogula-Kozlowska et al 2008;Cho et al 2009). …”
Section: Introductionmentioning
confidence: 99%